BASIC ARABIC LANGUAGE LEARNING AND COGNITIVE DEVELOPMENT IN EARLY CHILDHOOD: A DEVELOPMENTAL PSYCHOLOGY PERSPECTIVE - Sugeng Riyadi; Purwanto; Ahmadi (Al-ATHFAL: Jurnal Pendidikan Anak, 2025)
Language learning in early childhood plays a crucial role in shaping cognitive development. In Islamic early childhood education, basic Arabic language learning is not only positioned as a religious medium but also as a pedagogical instrument that supports children’s cognitive growth. This article aims to analyze the relationship between basic Arabic language learning and early childhood cognitive development from the perspective of developmental psychology. Employing a qualitative approach through library research and conceptual analysis, this study examines theories of cognitive development and their relevance to early Arabic language instruction in Islamic preschool settings. The findings indicate that basic Arabic learning activities, particularly vocabulary recognition, phonological awareness, and symbolic association through play-based learning, significantly contribute to cognitive abilities such as memory, classification, symbol recognition, and early abstract thinking. These findings align with Piaget’s cognitive developmental stages and Vygotsky’s sociocultural theory, which emphasize language as a fundamental tool for thought and social interaction. Therefore, basic Arabic instruction for young children should be designed developmentally appropriate, contextual, and enjoyable to function not merely as linguistic exposure but also as a cognitive stimulation strategy in Islamic early childhood education.